The Impacts of Stage Fright on the Selected Grade 12 Performing Arts Students in Bestlink College of the Philippines: Vol.3, No.1D (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The impacts of stage fright need much more attention than we thought; waiting can make our future brighter than we think. It specifically seeks the demographic profiles of the respondents like age and gender and the impacts of stage fright based on their confidence, passion, and experience; we wanted to aim and discover the right way to turn everything around upside down from the bad side and the good side of having a stage fright; specifically, this study was limited only for the selected 15 respondence from grade 12 Performing Arts student of Bestink College of the Philippines. Using the Questionnaire, we’ve complied the detailed data from their demographic profiles to their opinionated answers. To sum it up, of the 15 respondents, we got an overall weighted mean of 3.47 Agrees, based on a Likert Scaled formula by Ali and Bhaskar (2016). That is why we need to take courage that while performers suffer from mental pain, some people tend to seek that every action reacts because it is yet in life Experience will be our best teacher in the world.
Keywords: Impacts of Stage Fright; Experience